Is the universe indifferent? Should we care? - Kahane, G (Wiley, 2021)
The scientific worldview is often claimed to reveal a universe chillingly indifferent to human suffering. But it’s unclear what it means to describe the universe as indifferent, or what a non-indifferent universe would be like. I suggest that the relevant contrast isn’t simply that between God and His absence, nor is the complaint about indifference focused on the lack of a kind of cosmic concern. At its heart is the idea of a mismatch between world and value. Although the causal forces governing our world are ‘blind’, they nevertheless do partly align with value. Still, our world is so arranged that senseless suffering is depressingly common, and the rosy non-indifferent counterfactual won’t contain such evil. I argue, however, that it is a mistake to long for such an alternative: it must either involve an upside-down moral order, or would be a world from which we, and those who senselessly suffer, will be absent.